2015
DOI: 10.2527/jas.2014-8522
|View full text |Cite
|
Sign up to set email alerts
|

Age at puberty, ovulation rate, and uterine length of developing gilts fed two lysine and three metabolizable energy concentrations from 100 to 260 d of age1

Abstract: The objective of this study was to determine the effect of ad libitum feeding diets differing in standard ileal digestible (SID) lysine and ME concentrations that bracket those fed to developing gilts in U.S. commercial settings. Average SID lysine and ME concentrations in diets currently fed to developing gilts were obtained from a poll of the U.S. commercial swine industry. Crossbred Large White × Landrace gilts (n = 1,221), housed in groups, were randomly allotted to 6 corn-soybean diets in a 2 × 3 factoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 14 publications
6
14
0
Order By: Relevance
“…It should be noted that overall LGR of gilts in the current study would be considered low growth when compared with typical studies with commercial gilts (Amaral Filha et al, 2009;Bortolozzo et al, 2009). This is reflective of the fact that SID lysine contents in current diets are 15 to 30% less (high and low SID lysine-to-ME ratio diet, respectively) than in typical diets fed to gilts in finishing (Calderón Díaz et al, 2015b). Lents et al (2013) showed that gilts with greater LGR at 21 wk of age reached puberty earlier and that this was independent of backfat, which is consistent with previous research (Patterson et al, 2002).…”
Section: Results and Discussonsupporting
confidence: 87%
See 2 more Smart Citations
“…It should be noted that overall LGR of gilts in the current study would be considered low growth when compared with typical studies with commercial gilts (Amaral Filha et al, 2009;Bortolozzo et al, 2009). This is reflective of the fact that SID lysine contents in current diets are 15 to 30% less (high and low SID lysine-to-ME ratio diet, respectively) than in typical diets fed to gilts in finishing (Calderón Díaz et al, 2015b). Lents et al (2013) showed that gilts with greater LGR at 21 wk of age reached puberty earlier and that this was independent of backfat, which is consistent with previous research (Patterson et al, 2002).…”
Section: Results and Discussonsupporting
confidence: 87%
“…The frequency distribution for first estrus in the current study (Figure 1) clearly shows this was not the case. When approximately 1,200 commercial gilts in Iowa were subjected to direct boar contact beginning at 160 d of age, a wide range in age at first estrus (160 to 265 d of age) was observed (Calderón Díaz et al, 2015b) with 3 distinct subpopulations of gilts defined as early responders, midresponders, and late responders (Vallet, 2015). Gilt stimulation programs often involve remixing gilts every 2 wk to stimulate the onset of estrus in these mid and late responders (Levis, 2000;Soede et al, 2006).…”
Section: Results and Discussonmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial study was conducted with six diets fed ad libitum that contained two SID lysine and three metabolizable energy (ME) concentrations that bracketed those currently used by commercial swine herds in the USA. Growth rates, body composition and age at puberty did not differ (Calderón Díaz et al, 2015a, 2015b. Results indicated that gilts compensated for differences in ME between diets by altering feed intake.…”
Section: Itemmentioning
confidence: 86%
“…The feeding model used in the present study recognized that intake is highly regulated for energy and nutrient input (NRC Swine, 2012). Energy density is a key modifying dietary intake factor in pigs, however, amino acid dietary content that is less than that recommended by the NRC (NRC, 2012) can also be partially compensated for by increasing intake (Calderón Díaz et al, 2015a, 2015b). The diet model of the present study involved increasing diet total NDF to ultimately result in a maximum dietary intake.…”
Section: Discussionmentioning
confidence: 99%